Preparation of microbubble suspensions by co-axial electrohydrodynamic atomization. - Farook, U; Zhang, H; Edirisinghe, M; Stride, E; Saffari, N (2007)
In this paper we report a novel method, based on co-axial electrohydrodynamic jetting, for the preparation of microbubble suspensions containing bubbles <10 microm in size and having a narrow size distribution. No selective filtration is necessary and the suspensions are produced directly by the process. To demonstrate the method, glycerol was used as the liquid medium, flowing in the outer needle of the co-axial twin needle arrangement and undergoing electrohydrodynamic atomization in the stable cone-jet mode while air flowed through the inner needle at the same time. At zero applied voltage a hollow stream of liquid flowed from the outer needle. When the applied voltage was increased, eventually the hollow stream became a stable cone-jet and emitted a microthread of bubbles, which were collected in a container of glycerol to obtain microbubble suspensions. The size of the microbubbles was measured via optical microscopy and laser diffractometry. Several microbubble suspensions were prepared and characterised and the size distribution was found to be critically dependent on the ratio (n) of flow rates of liquid/air and, in particular the flow rate of the air. At n=1.5, with the flow rate of air set at approximately 1.7 microl/s, a microbubble suspension containing bubbles in the size range 2-8 microm was obtained.